2017
DOI: 10.3390/app7090931
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Pore Structure of Coal Associated with Sc-CO2 Extraction during CO2-ECBM

Abstract: Supercritical CO 2 (Sc-CO 2 ), a supercritical solvent, can extract small organic molecules (fluid) from coal, changing pore structures to affect gases storage and migration in the coal matrix. Five undeformed coals before and after the second coalification jump were collected to simulate Sc-CO 2 extraction performed with supercritical extraction equipment. Pore structures of the samples before and after Sc-CO 2 extraction were characterized using mercury porosimetry. The results show that there are significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Generally, the micropore volume has exhibited a decreasing trend after ScCO 2 exposure, when the intensity of the matrix swelling has been observed to be stronger than the other effects. Instead, the micropore volume has been found to increase (Chen et al., 2017; Zhang et al., 2017a). However, for the dry coals, numerous studies have shown that ScCO 2 exposure cannot significantly change the PSD of the micropores of coals (Figure 4).…”
Section: Effects Of Scco2 On the Pore Morphology Of Coalsmentioning
confidence: 99%
“…Generally, the micropore volume has exhibited a decreasing trend after ScCO 2 exposure, when the intensity of the matrix swelling has been observed to be stronger than the other effects. Instead, the micropore volume has been found to increase (Chen et al., 2017; Zhang et al., 2017a). However, for the dry coals, numerous studies have shown that ScCO 2 exposure cannot significantly change the PSD of the micropores of coals (Figure 4).…”
Section: Effects Of Scco2 On the Pore Morphology Of Coalsmentioning
confidence: 99%
“…When coal is exposed to ScCO 2 , the ScCO 2 is incorporated into the coal and it rearranges the coal's structure [19]. It is generally agreed that ScCO 2 can change the pore morphology of coal irreversibly, including pore volume, pore size distribution, surface area, and pore connectivity [20,21]. Additionally, ScCO 2 is an organic solvent and can mobilize some of the organic matter in the coal.…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 injected into coal beds enhances coal bed methane (CBM), taking advantage of competitive adsorption. CO 2 geological storage-enhanced coal bed methane recovery (CO 2 -ECBM) is a new technology that has been proposed to implement CO 2 storage in coal beds and also enhance the recovery of CBM [2,3]. However, the injection capacity and storage potential of CO 2 in coal beds will decrease as a result of coal swelling deformation [4][5][6].…”
Section: Introductionmentioning
confidence: 99%